Perbandingan Peringkat Pertumbuhan Ekonomi dan Peringkat Kemiskinan Kabupaten Batang Hari dengan Kabupaten Muaro Jambi - Niki Kosasi; Ahmad Feri Fadli (LEMBAGA PENELITIAN DAN PENGABDIAN KEPADA MASYARAKAT UNIVERSITAS GRAHA KARYA MUARA BULIAN, 2020)
The purpose of this study was to find out more about the development of economic growth and poverty development in Batang Hari Regency, the development of economic growth and poverty development in Muaro Jambi Regency, the economic growth rank and the poverty ranking of Batang Hari Regency with Muaro Jambi Regency, and the comparison of economic growth rankings and poverty ranking of Batang Hari Regency with Muaro Jambi Regency. The data collection method uses library research and online data search. The data analysis method used is descriptive qualitative analysis method. The data analysis tools used are the theory of growth / development, the formula for growth / development and the theory of ranking The results showed that the development of economic growth in Batang Hari Regency tends to decline and the development of poverty in Batang Hari Regency tends to increase every year. The development of economic growth in Muaro Jambi Regency has fluctuated and the development of poverty in Muaro Jambi Regency has increased. The economic growth ranking and poverty ranking of Batang Hari Regency with Muaro Jambi Regency, for the economic growth ranking of Batang Hari Regency is in the 5th place (five) and the economic growth rank of Muaro Jambi Regency is at 6th (sixth), while the poverty ranking for Batang Regency is Hari is in the 6th (sixth) rank and the poverty rank of Muaro Jambi Regency is in the 3rd (third) rank calculated from the average. Comparison of the economic growth ranking and poverty ranking of Batang Hari Regency and Muaro Jambi Regency, for the economic growth ranking it tends to be equally declining, but the economic growth ranking of Batang Hari Regency is higher on average than the economic growth rank of Muaro Jambi Regency and the poverty rank of Batang Regency Days are lower than the poverty rank of Muaro Jambi Regency which fluctuates every year.